The book that no one wanted to read - Ayoade, Richard, 1977- (Walker Books US, a division of Candlewick Press, 2023)
"The life of a book isn't easy, especially when people judge you by your cover (not every book can be adorned with sparkly unicorns!). And this narrator should know--it's the book itself, and it has a lot of opinions. It gets irritated when readers bend its pages back, and it finds authors quite annoying. But it does have a story to tell. Through witty direct address and charming illustrations, readers meet a book that has never been read, with a cover the boring color of a school lunch table and pages so dry they give bookworms indigestion. But what happens when this book meets you, a curious reader? Multitalented author Richard Ayoade and award-winning illustrator Tor Freeman bring to life a hilariously subversive take on the nature of books and reading, with a heartening theme of finding the courage to tell our own stories. Readers of all ages will be delighted by the myriad bookish references and laughs on every page."--